2013
DOI: 10.1186/2051-5960-1-32
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously regulated Dab2 worsens inflammatory injury in experimental autoimmune encephalomyelitis

Abstract: BackgroundNeuroinflammation regulates both disease pathogenesis and repair in multiple sclerosis. In early multiple sclerosis lesion development, neuroinflammation causes demyelination and axonal injury, the likely final common determinant of disability. Here we report the identification of a novel neuroinflammatory mediator, Disabled-2 (Dab2). Dab2 is an intracellular adaptor protein with previously unknown function in the central nervous system.ResultsWe report that Dab2 is up-regulated in lesional macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 48 publications
0
39
1
Order By: Relevance
“…They also found that Dab2-deficient mice had less severe EAE than wild-type littermates (Jokubaitis et al, 2013). Dab-2 is an important molecule in cells and follows multiple cascades related to cell activation, but its role should be studied further.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They also found that Dab2-deficient mice had less severe EAE than wild-type littermates (Jokubaitis et al, 2013). Dab-2 is an important molecule in cells and follows multiple cascades related to cell activation, but its role should be studied further.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Jokubaitis et al (2013) reported an association between Dab-2 and nitric oxide generation in an EAE model, with Dab-2 detected concomitantly with inducible nitric oxide synthase (iNOS) in EAE and multiple sclerosis brain lesions. They also found that Dab2-deficient mice had less severe EAE than wild-type littermates (Jokubaitis et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…IFN-Îł, which promotes M1 phenotypic polarization in macrophages, induces the expression of IFN consensus sequence-binding protein (ICSBP, also known as IRF8), which in turn transcriptionally represses Dab2 (40). Upregulation of DAB2 was observed in spinal cord lesions in murine experimental autoimmune encephalomyelitis (41).…”
Section: Introductionmentioning
confidence: 98%
“…MAT protects neurons and astrocytes against focal cerebral ischemia by inhibiting the expression of NF-ÎșB [22] or through its anti-oxidant and anti-apoptotic properties [23]. Further, MAT treatment improves motor function and increases axonal density in mice with spinal cord injury, likely through inhibition of epidermal growth factor receptor signaling [24]. However, whether MAT can induce neuroregeneration in EAE has not been studied.…”
Section: Introductionmentioning
confidence: 93%